Resistance phenotypes and genomic features of Mycobacterium seoulense isolates - Jin Zhao; Xinli Shen; Lulu Jin; Songjun Ji; Xinling Pan (Frontiers in Cellular and Infection Microbiology)
BackgroundMycobacterium seoulense (M. seoulense) is an emerging pathogen increasingly associated with infections; however, its resistance phenotypes and genomic characteristics remain largely unknown.MethodsSeven M. seoulense isolates were collected from clinical samples. Drug susceptibility testing was conducted using Sensititre™ SLOMYCO2 susceptibility plates. Whole genome sequencing and supporting bioinformatics analyses were performed to analyze the genomic features.ResultsAll M. seoulense isolates (n=7) exhibited growth on 7H10 agar medium containing thiophenecarboxylic acid hydrazide or p-Nitrobenzoic acid, with marked diversity in growth rates in liquid culture. All strains exhibited high minimum inhibitor concentrations (MICs) for minocycline (>8 μg/mL), doxycycline (>8 μg/mL), and amikacin (16-32 μg/mL). The MICs for linezolid, rifabutin, moxifloxacin, ciprofloxacin, streptomycin, clarithromycin, and rifampicin varied among the isolates. High levels of genomic diversity were noted among these strains concerning genome-called single nucleotide polymorphisms and average nucleotide identity. In total, 4,282 genes were shared across all genomes, while 315 unique genes were restricted to one strain. Comparative genomic analysis identified two unique virulence genes encoding a catalase enzyme and a protein involved in capsule biosynthesis and transport. Additionally, all M. seoulense strains demonstrated the ability to survive within macrophages.ConclusionThe clinical M. seoulense isolates analyzed in this study exhibited varying levels of antibiotic susceptibility, suggesting the potential need for susceptibility testing to guide clinical treatment. Genomic features of these isolates indicated that they are likely pathogenic non-tuberculous mycobacterium, highlighting a need for closer epidemiological monitoring.